The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1177/1740774512447898
|View full text |Cite
|
Sign up to set email alerts
|

A statistical approach to central monitoring of data quality in clinical trials

Abstract: Central statistical monitoring can both optimize on-site monitoring and improve data quality and as such provides a cost-effective way of meeting regulatory requirements for clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(108 citation statements)
references
References 13 publications
2
106
0
Order By: Relevance
“…From a process perspective, the use of statistical methods [4][5][6] is essential to identify data anomalies. Digit preferences, for example, can signal potential data integrity concerns.…”
Section: Methodsmentioning
confidence: 99%
“…From a process perspective, the use of statistical methods [4][5][6] is essential to identify data anomalies. Digit preferences, for example, can signal potential data integrity concerns.…”
Section: Methodsmentioning
confidence: 99%
“…53 Centers with outrageous information irregularity scores are deserving of further examination, with the point of clarifying the distinctions, retraining the site staff if required, or -in the most dire outcome imaginable -to reveal a misrepresentation that would some way or another stay undetected. Hence high data inconsistency scores are a statistical finding with no implied value judgment and should not be interpreted as a "data quality" index.…”
Section: ) Use Of Technologymentioning
confidence: 99%
“…Building on prior research, [3][4][5][6][8][9][10] TransCelerate tested statistical-monitoring methods on a biopharmaceutical industry-sponsored clinical study database under conditions partially mimicking those found during real-world study conduct. The objective of this experiment was to detect data anomalies suggestive of noncompliance, but it primarily focused on intentionally fabricated data because of the potential difficulty in detecting this type of noncompliance.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 One strategy being used is statistical monitoring, or the use of various statistical methods during study conduct to detect data anomalies suggestive of fabrication or noncompliance. 1,[3][4][5] The multicentric nature of most clinical trials offers an opportunity to check the plausibility of data from one site against data from all other sites. 3 Statistical monitoring relies on the highly structured nature of data because each protocol is expected to be implemented consistently at all sites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation